PSYCHOLOGY OF ADOLESCENT WOMEN WHO EXPERIENCE PREMENSTRUAL SYNDROME AT JUNIOR HIGH SCHOOL 3 TUBAN - nurul, siti; sumiatin, titik; su'udi, su'udi (Global Ten Public Health and Nursing Journal, 2023)
Menstruation is often regarded as a problem in the lives of girls who will enter adolescence. Most women will experience discomfort before menstruation, one of which is premenstrual syndrome (PMS). From a preliminary survey conducted on students of SMP N 3 Tuban, it was found that 4 out of 5 students had premenstrual syndrome (PMS). The purpose of this study was to determine the psychological picture of adolescents with premenstrual syndrome at Junior High School 3 Tuban. The research method used in writing this scientific paper is descriptive analysis with a cross sectional approach. The population in this study were students of Junior High School 3 Tuban in the academic year 2021-2022 with a total of 95 respondents and the sampling technique used was total sampling with a sample of 95 students. Analysis of the data used the frequency test. Using the instrument with a questionnaire. The results of this study showed that from 95 respondents, 54 respondents (56.8%) experienced premenstrual syndrome with mild severity, with almost all 83 respondents (87.4%) experiencing irritability, most of 69 respondents (72.6%) experiencing anxiety. , and almost all of the 82 respondents (86.3%) experienced psychological problems with withdrawing The importance of understanding reproductive health education and education about premenstrual syndrome such as causes, effects, and how to deal with premenstrual syndrome. Where it can reduce the severity of premenstrual syndrome experienced